Bem-estar no consumo de moda plus size - Büttner, Ana Julia (2019)
This research aims to discuss the concept of well-being as regards the consumption of plussize women’s fashion. To achieve this objective, constructs related to well-being, fashion awareness and fashion consumption are explored vis-à-vis qualitative research, by way of indepth interviews and iconography. The conclusions emerging from this study comprise three marketing-related applications: the first one centers on the product development of a plus-size brand, the second refers to brand image, and the third relates to fashion retail sales training.